Berlin days - Clare, George 1920-2009 (Pan Books, 1990)
Continues the memoir begun in Last Waltz in Vienna. In 1946 the author was posted to Berlin where he worked as a British intelligence officer, and his experiences form the basis of this book, providing a vivid portrait of the city and its post-war inhabitants.